Identification and characterization of putative effectors from Plasmodiophora brassicae that suppress or induce cell death in Nicotiana benthamiana - Zhan, Zongxiang; Liu, Huishan; Yang, Yao; Liu, Shuang; Li, Xiaonan; Piao, Zhongyun (Frontiers in Plant Science, 2022)
Clubroot, caused by Plasmodiophora brassicae, is a major disease of crucifers. Effector proteins are important virulence factors in host recognition of pathogens and the interactions between pathogens and hosts. Secretory proteins, as effector candidates, have been studied in the interaction between Plasmodiophora brassicae and its hosts. In this study, 518 secretary proteins were screened from the Plasmodiophora brassicae genome. A total of 63 candidate effectors that induce or suppress cell death were identified using agroinfiltration-mediated transient expression in Nicothiana benthamiana. The candidate effectors, Pb4_102097 and Pb4_108104 showed high expressing level in the stage of rest spore maturity, could induce cell death and were associated with H2O2 accumulation in N. benthamiana leaves. In addition, 55 candidate effectors that could suppress BAX (Bcl-2-associated X protein) induced cell death, and 21 out of which could suppress the immunity caused by bacterial pathogen Pseudomonas syringae pv. tomato strain DC3000 expressing avrRps4 in Arabidopsis. Based on the expression pattern in different stages, 28 candidate effectors showed high expression levels during the primary and secondary infection stage. Five candidate effectors containing the RXLR motif functioned in the cytoplasm and cell membrane.